The Characteristics of Liquid Soap with Additional Variations of Moringa Seed Extract (Moringa oleifera L.) - Andrew Setiawan Rusdianto; Atika Yulianti; Sony Suwasono; Andi Eko Wiyono (Food, Agriculture and Natural Resources - NETWORKS, 2021)
Soap is a cleaning compound formed from the reaction between fatty acid compounds and alkaline bases. Various types of soap have been circulating in the market, one of which is liquid soap. Liquid soap that has antibacterial abilities is needed by many people. Moringa seed extract is one of the natural ingredients that can be used as an active ingredient in making liquid soap because it can inhibit bacterial growth. This study aims to determine the effect of variations in the addition of extracts and to obtain the best extract concentration treatment on physical, chemical, and organoleptic. The addition of moringa seed extract used was administered at 3%, 5%, and 7%. Data analysis was carried out by applying the ANOVA (Analysis of Variance) with a significant level of 5%. The De Garmo method was used to formulate the best liquid soap recommendation among various treatments. The results showed that the addition of moringa seed extract had a significant effect on the parameters of free alkali content, viscosity, specific gravity, antibacterial activity, and organoleptic. The best recommendation for liquid soap is a soap with a concentration of 7% with specific gravity characteristics of 1.066 g/ml, the viscosity of 1.983 cP, pH value of 10.53, foaming power of 5.63 cm, foam stability of 94.64%, and free alkali content of 0.023%, and the antibacterial ability against S. aureus bacteria (clear zone) was 19.17 mm.